The Impact of Workload, Work Discipline, and Work Environment on Indomaret Employee Performance - Novita, Lola (YUME : Journal of Management, 2024)
Employee performance is a crucial factor in achieving organizational success, especially in the retail sector, where efficiency and service quality directly affect customer satisfaction. This study aims to analyze the impact of workload, work discipline, and work environment on employee performance at Indomaret. A quantitative research approach was used, collecting data through surveys distributed to employees. The findings indicate that workload has a significant effect on performance, where excessive workload leads to decreased productivity and job satisfaction. Work discipline plays a crucial role in ensuring employees adhere to company policies, directly improving efficiency and service quality. Furthermore, a conducive work environment fosters motivation, reduces stress, and enhances overall employee performance. The study highlights the importance of balancing workload, enforcing strict discipline, and creating a supportive work environment to optimize employee performance in the retail industry. Keywords: Workload, Work Discipline, Work Environment, Employee Performance, Retail Industry